Vicarious trauma and natural disasters a transcendental phenomenological analysis of the experiences of families of typhoon Haiyan survivors - Calleja, Mendiola Teng (Philippine Journal of Psychology, 2015)
Using transcendental phenomenology, we examined the experience of vicarious trauma in the context of natural disasters. We specifically looked at the narratives of domestic migrants whose family members were Typhoon Haiyan survivors. Findings show that the survivors’ families experienced painful and intrusive psychological distress. The gravity of the pain and loss experienced by the participants was relative to the amount of pain, loss, or damage sustained by the subject of their attachment. Vicarious trauma was experienced as a void-filling phenomenon occupying the emotional space created by the physical distance of the participants from their families experiencing the disaster. This phenomenon and the concurrent traumatic experience improved as the participants made sense of the significance of the event in their lives. Our findings may help in developing interventions to address the effects of vicarious trauma on families of disaster victims and survivors.